'The miseries of others': boxing in Hogarth's Second Stage of Cruelty. Issue 2 (2nd April 2020) - Skala, Doreen
ABSTRACT: The violence inherent in boxing has been a topic of public discourse since the early days of the sport, as has its supposed effect on society. In 1751, artist and social commentator William Hogarth weighed in by including boxing references in his four-part work addressing cruelty in 1740s London. In his Second Stage, dedicated to cruelty to animals, he somewhat incongruously includes a poster for a prizefight. This essay examines boxing in early-to-mid Hanoverian London to reveal why Hogarth chose to include this particular fight, using a variety of sources including an unpublished eyewitness account. This examination will allow us to better understand a transformational period in the sport of boxing and its place in 1740s London society.